CHARACTERISTIC OF SURFACE HYDROLIPIDE SKIN FILM IN CHILDREN OF FIRST YEAR OF LIFE WITH TOXIC ERITEMOUS IN ANAMNESE - Татьяна Александровна Нагаева; Наталия Ивановна Басарева; Виктор Александрович Желев; Дарья Алексеевна Пономарева (The Publishing House Medicine and Enlightenment, 2018)
Toxic erythema of newborns is referred to borderline states and is considered as the first manifestation of allergy. The formation of a complete epidermal skin barrier depends on the lipid and vitamin composition of the surface hydrolyzed film (SHLF) of the skin. The purpose of the study - to study the peculiarities of the lipid and fat-solvable vitamins content in the SHLF of the skin of newborns and infants with toxic erythema in the anamnesis. Materials and methods. There was carried out a complex clinical and laboratory study of 46 healthy children and 34 children with elements of toxic erythema on the body and extremities. Biochemical analysis of the superficial lipid skin film was carried out on the 1st and 6th days of life, as well as at the end of 1, 6, 9 and 12 months. Results and conclusions. When comparing the parameters of SHLF skin of children with manifestations of toxic erythema with those in healthy children, significant differences were found on the first day of life. Changes in the lipid and vitamin spectrum of SHLF in children with manifestations of toxic erythema observed in the early neonatal period were expressed in a high level of triacylglycerols, fat acids, phospholipids and β-carotene and a low percentage of cholesterol, α-palmitate and α-tocopherol. By the end of the first year of life, the composition of the SHLF of the skin of children with manifestations of toxic erythema in the anamnesis practically did not differ from the one in the group of healthy children.